Living Hadith on the Samadiyah Tradition in Langsa Aceh - Fajriatul Ula; Nur Raihan; Fadil, Muhammad Reza (Al-Bukhari : Jurnal Ilmu Hadis, 2022)
This study discusses the Samadiyah tradition or the practice carried out by the community to pray for the deceased person. The Samadiyah tradition in Aceh is based on an Acehnese understanding that death is a tough journey so it needs to be prepared, assisted and supported by living families. The purpose of this study is to look at the practice of the samadiyah tradition in Aceh, especially Langsa City and to review the hadiths that related to the samadiyah tradition. The type of research used is field research with a phenomenological approach and data collection methods by means of observation, interviews, and documentation. The results of this study can be concluded that the practice of the samadiyah tradition in Aceh start by reading istighfar, shalawat to Rasulullah Saw, reading Surah Al-Ikhlas, Al-Falaq, An-Nas, Surat al-Fatihah then reading tahlil (reading the sentence Laa ilaha illallah ) and ended with a prayer by asking and hoping that the prayer for the soul can be accepted and provide benefits to the deceased person. Samadiyah activities in Aceh, Langsa City, were led by Teungku who has specialty and who had implemented the samadiyah reading by profession and also had learnt a tarekat from specific tarekat scholars (Mursyid). This living hadith study found out that, this tradition is the result of community practice of the traditions of the Prophet taught by tarekat scholars. The Ulama or Teungku has an important role as a connector between the hadith text and society, which is then executed in the form of practice or practice continuously